An Analysis of Writing Assignments in German Textbooks Schritte international neu I and II - Jennasombut, Supatcha (Journal of Letters, 2020)
The purpose of this research is to analyze the writing assignments in German textbooks, Schritte international neu I and II, which are used in German classes at the Faculty of Humanities, Srinakharinwirot University. Rainer Bohn’s theory of writing assignment classification is used as an analytical framework. According to this theory, writing assignments can be classified into two main types: writing assignments for developing vocabulary, grammar, listening skills, speaking skills, and reading skills; and assignments for developing writing skills. It is found that the writing assignments in these two textbooks are mostly for vocabulary and grammar review. The types of writing exercises found are cloze tests, sentence completion, writing preparation for conversation, and answering questions from listening or reading exercises. Students are usually required to write at word and sentence level. It is also found that there are more writing assignments for developing speaking and listening than for reading, and there are many fewer assignments for developing writing. Most assignments for writing development are reproductive writing assignments. This is to give students a framework for their writing assignments and to help them practice using vocabulary, phrases, idioms and sentences from the source. In the second textbook, productive writing assignments and writing assignments for specific purposes, i.e., writing greetings for different occasions, have been added.